Alterações produtivas, morfoanatômicas e fisiologicas de Beta vulgaris L. ssp. vulgaris var. saccharifera tratadas com Cryptococcus laurentii, Pichia pini e silicato de cálcio e desafiadas com Cercospora beticola - Barabasz, Renata Filler (2021)
The cercospora stain mainly attacks the older leaves, in which necrotic spots are formed on the adaxial and abaxial surfaces of the leaves, reducing their photosynthetic area and consequently the accumulation of energy, their sugar production and the total loss of yield. In view of this, this study aimed to evaluate the effect of yeasts and calcium silicate on morphological and anatomical characteristics and agronomic characteristics of sugar beet challenged with Cercospora beticola. The treatments were Cryptococcus laurentii, Pichia pini, calcium silicate, C. laurentii + calcium silicate, P. pini + calcium silicate and stylized water (control) in concentrations of 1 x 108 yeast cells mL-1 and 3.8 g dm3 of calcium silicate. The characteristics evaluated were: plant height, fresh and dry mass of aerial part, hypocotyl and root, number of leaves, leaf area and total soluble solids content (°Brix) of the hypocotyl. To assess anatomical and histological changes, an experiment was implemented using a 4x2 factorial scheme, with four treatments (calcium silicate, P. pini, C. laurentii and control) and two conditions (presence and absence of the pathogen). The characteristics evaluated were the thickness of the palisade parenchyma, thickness of the lacunous parenchyma, thickness of the epidermis of the adaxial and abaxial surfaces of the leaf blade, diameter of the petiole xylem vessels and the diameter of the main root xylem vessels. For the variables fresh weight of the hypocotyl, °Brix and dry mass of the hypocotyl, there was an interaction between treatments. It was found that there were changes in the thickness of the palisade parenchyma of the leaf's abaxial face and in the diameter of the vessels of the root xylem. It was not possible to observe changes in the tissue organization in the tested treatments, however, in certain points of the cellular structure of leaves of plants treated with calcium silicate in the presence of the pathogen, the presence of lignin in the adaxial and abaxial surfaces of the leaf blade can be observed, indicating resistance induction in the plant by recognizing the presence of the pathogen. Thus, it is concluded that calcium silicate and the yeasts C. laurentii and P. pini did not favor the improvement of agronomic characteristics, as well as in the cellular structure of sugar beet, even when challenged with C. beticola.